Driver’s physiological measures with in vehicle secondary distraction: a systematic review - Nor Kamaliana Khamis,; Muhammad Aizat Shamsudin,; Nurainaa Kabilmiharbi,; Nor Azila Noh, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Driving vehicles has become more complex. Thus, drivers who are not engaged with any non-related driving activities, that is performing in-vehicle secondary task, are unusual nowadays. Statistics also shows the higher number of crashes come from distracted driving. In addition, currently, there is limited review have been done to compile and review the physiological method, driving distraction and its effect on the driver. Therefore, this paper aims to review the effect of driver’s in-vehicle distraction and secondary task during driving on driver’s health and safety. A systematic search was conducted on the basis of the preferred reporting items for systematic reviews by using PRISMA guidelines. Any criteria were imposed for the included sample. The search was focused on in-vehicle secondary task and distraction. Results showed that 21 articles investigated the major ability for in-vehicle secondary task distraction using physiological measures. Findings showed a significant effect of the in-vehicle secondary task and distraction on driver’s condition. Drivers’ characteristics such as their experience and age are also factors in determining the effect of distraction and secondary tasks on their condition. However, further studies are needed to understand the physiological effect of secondary task on young driver’s condition due to the relatively higher number of crash rates from those at a young age.